The contribution of shadow insurance to systemic risk - Leong, Soon Heng; Pellegrini, Carlo Bellavite; Urga, Giovanni (Journal of Financial Stability, 2020)
Shadow insurance is a regulatory loophole exploited by certain insurance groups to increase risk exposure, potentially destabilising the financial system. In this paper, we evaluate the contribution of shadow insurance to systemic risk of the global financial sector using a sample of 215 international insurance entities covering the 2004–2017 period. We detect shadow insurance by examining every reinsurance agreement on the Schedule S filings. Using both ΔCoVaR and SRISK measures, we find that the practice of shadow insurance is a significant driver of global systemic risk.